A unique high mechanical strength dialdehyde microfibrillated cellulose/gelatin composite hydrogel with a giant network structure. Issue 76 (29th July 2016) - Zheng, Xuejing; Zhang, Qiannan; Liu, Jie; Pei, Ying; Tang, Keyong
Abstract : A giant network structure was constructed throughout the dialdehyde microfibrillated cellulose (DAMFC)/gelatin composite hydrogel by Schiff base formed through the crosslinking reaction between the aldehyde groups of DAMFC and amino groups of gelatin. Abstract : Microfibrillated cellulose (MFC) with diameters less than 100 nm and a three-dimensional network structure was produced through high-pressure homogenization. MFC was surface modified by periodate to prepare dialdehyde microfibrillated cellulose (DAMFC). DAMFC/gelatin composite hydrogel was prepared by mixing DAMFC with gelatin solution. A Schiff base was formed through the reaction between the aldehyde groups of DAMFC and amino groups of gelatin; therefore, a giant three-dimensional network structure was formed in the composite hydrogel. Since the nano reinforcing agent DAMFC was covalently bonded to the matrix gelatin, the load could be efficiently transferred through the giant network, therefore, the composite hydrogel presented extremely high mechanical properties. The compression strength of DAMFC/gelatin 25/75 (wt/wt) hydrogel dramatically increased to 1.63 MPa, 41 times that of the pure gelatin. Morphology observation revealed that the pore size of the composite hydrogel could be regulated by the DAMFC oxidation level. The composite scaffold demonstrated a good swelling capacity and could successfully maintain its shape in buffer solution. It should be noted that the giant network is different from the double network or fiber reinforced hydrogel. The present work shows that by forming a giant network structure through chemical crosslinking with the reinforcing agent itself, an extremely high mechanical strength composite hydrogel could be obtained.